Direct Observation of Interfacial Dzyaloshinskii-Moriya Interaction from Asymmetric Spin-wave Propagation in W/CoFeB/SiO(2) Heterostructures Down to Sub-nanometer CoFeB Thickness - Chaurasiya, Avinash Kumar (Sci Rep, 2016)
Interfacial Dzyaloshinskii-Moriya interaction (IDMI) is important for its roles in stabilizing the skyrmionic lattice as well as soliton-like domain wall motion leading towards new generation spintronic devices. However, achievement and detection of IDMI is often hindered by various spurious effects. Here, we demonstrate the occurrence of IDMI originating primarily from W/CoFeB interface in technologically important W/CoFeB/SiO(2) heterostructures using Brillouin light scattering technique. Due to the presence of IDMI, we observe asymmetry in the peak frequency and linewidth of the spin-wave spectra in the Damon-Eshbach (DE) geometry at finite k wave-vectors. The DMI constant is found to scale as the inverse of CoFeB thickness, over the whole studied thickness range, confirming the presence of IDMI in our system without any extrinsic effects. Importantly, the W/CoFeB interface shows no degradation down to sub-nanometer CoFeB thickness, which would be useful for devices that aim to use pronounced interface effects.